The equation of a line in point slope form =
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
To put
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
into function notation, we need to get y by its self.
Lets say we had a point (2,2) and a slope of 3. Ok, now that we have our point and slope, lets turn point slope form into function notation.
![y - y_1 = m(x - x_1)](https://tex.z-dn.net/?f=y%20-%20y_1%20%3D%20m%28x%20-%20x_1%29)
![y - 2 = 3(x - 2)](https://tex.z-dn.net/?f=y%20-%202%20%3D%203%28x%20-%202%29)
![y - 2 = 3x - 6](https://tex.z-dn.net/?f=y%20-%202%20%3D%203x%20-%206)
![y = 3x - 6 + 2](https://tex.z-dn.net/?f=y%20%3D%203x%20-%206%20%2B%202)
![y = 3x - 8](https://tex.z-dn.net/?f=y%20%3D%203x%20-%208)
Change the y to f(x)
![f(x) = 3x - 8](https://tex.z-dn.net/?f=f%28x%29%20%3D%203x%20-%208)
<-----Function notation.
Answer:
x=4
y=3
Step-by-step explanation:
Answer:
56 that's easy.....
Step-by-step explanation:
....